Reflecting strategic and conforming gendered experiences of community health workers using photovoice in rural Wakiso district, Uganda - David Musoke; Charles Ssemugabo; Rawlance Ndejjo; Elizabeth Ekirapa-Kiracho; Asha S. George (BMC, 2018)
Abstract Background Community health workers (CHWs) are an important human resource in Uganda as they are the first contact of the population with the health system. Understanding gendered roles of CHWs is important in establishing how they influence their performance and relationships in communities. This paper explores the differential roles of male and female CHWs in rural Wakiso district, Uganda, using photovoice, an innovative community-based participatory research approach. Methods We trained ten CHWs (five males and five females) on key concepts about gender and photovoice. The CHWs took photographs for 5 months on their gender-related roles which were discussed in monthly meetings. The discussions from the meetings were recorded, transcribed, and translated to English, and emerging data were analysed using content analysis in Atlas ti version 6.0.15. Results Although responsibilities were the same for both male and female CHWs, they reported that in practice, CHWs were predominantly involved in different types of work depending on their gender. Social norms led to men being more comfortable seeking care from male CHWs and females turning to female CHWs. Due to their privileged ownership and access to motorcycles, male CHWs were noted to be able to assist patients faster with referrals to facilities during health emergencies, cover larger geographic distances during community mobilization activities, and take up supervisory responsibilities. Due to the gendered division of labour in communities, male CHWs were also observed to be more involved in manual work such as cleaning wells. The gendered division of labour also reinforced female caregiving roles related to child care, and also made female CHWs more available to address local problems. Conclusions CHWs reflected both strategic and conformist gendered implications of their community work. The differing roles and perspectives about the nature of male and female CHWs while performing their roles should be considered while designing and implementing CHW programmes, without further retrenching gender inequalities or norms.